Holy monstrosity: a study of François Mauriac’s Thérèse Desqueyroux - Leno, Olivia (Kansas State University, 2017)
In a world painted black and white, monsters are always evil and they always seek to destroy what is good, with or without reason. However, twentieth-century Catholic novelist François Mauriac, in his Thérèse Desqueyroux, proposes that the matter of monstrosity is not so easily defined. In a mysterious preface to the novel, Mauriac employs a Baudelarian epigraph that brings murkiness to this definition: “O Créateur ! peut-il exister des monstres aux yeux de celui-là seul qui sait pourquoi ils existent, comment ils se sont faits.. ” (13, italics original). Through the words of Baudelaire, Mauriac questions the nature of his protagonist Thérèse, a “semi-empoisonneuse,” and in the process of doing so, revolutionizes the Catholic novel and the role of women in literature. In this paper, I intend to prove that Mauriac’s departure from the typical Catholic novel and its clichéd protagonist brings complexity to feminine representation by analyzing a “monstrous” female protagonist. Through analysis of historical development of the Catholic novel, as well women’s roles (inside and outside of literature) during and after World War I, this paper seeks to demonstrate that François Mauriac’s representation of women is groundbreaking in comparison to literary works at the time. Mauriac dismisses the pious prototype of the Catholic novel and instead choses a dark and “monstrous” woman as his creation. This paper will examine Thérèse’s refusal of societal roles as wife and mother, as well as Mauriac’s tone, in order to demonstrate the revolutionary portrayal of a monster as his protagonist.
Keywords: Women; Monstrosity; Thérèse Desqueyroux; BourgeoisMauriac